2020
DOI: 10.1155/2020/2387823
|View full text |Cite
|
Sign up to set email alerts
|

Deep Belief Network for Feature Extraction of Urban Artificial Targets

Abstract: Reducing the dimension of the hyperspectral image data can directly reduce the redundancy of the data, thus improving the accuracy of hyperspectral image classification. In this paper, the deep belief network algorithm in the theory of deep learning is introduced to extract the in-depth features of the imaging spectral image data. Firstly, the original data is mapped to feature space by unsupervised learning methods through the Restricted Boltzmann Machine (RBM). Then, a deep belief network will be formed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…of the methods in this article, it can be observed that the two methods can both be used to evaluate the continuity level of the detection results of different image features, but the method put forward in this paper can distinguish the images more effectively. In addition, the evaluation time of the method put forward in this paper is less than that of the method described in literature [11][12][13][14]. Hence, it has significant advantages in the application.…”
Section: Settings Of the Main Parametersmentioning
confidence: 95%
“…of the methods in this article, it can be observed that the two methods can both be used to evaluate the continuity level of the detection results of different image features, but the method put forward in this paper can distinguish the images more effectively. In addition, the evaluation time of the method put forward in this paper is less than that of the method described in literature [11][12][13][14]. Hence, it has significant advantages in the application.…”
Section: Settings Of the Main Parametersmentioning
confidence: 95%
“…The majority of those people had diabetes and were being handled with steroids for SARS-CoV-2 disease, which could have caused them more vulnerable to fungal infection. Mucormycosis seems to be more prevalent among people who have a low immune system or who have had a bone marrow transplant with fewer neutrophils [35] [85]. COVID-19's introduction has resulted in a slew of new illnesses and problems [16] [63].…”
Section: Black Fungus Infection In India: Mucormycosis Spreading In I...mentioning
confidence: 99%
“…The fungus detection system required a powerful feature extraction method in order to deal with all of these difficult difficulties. Dalal et al [35] presented Histogram of Oriented Gradients as a method for detecting persons (HOG). The extraction of features from photos was accomplished using this methodology.…”
Section: Feature Extractionmentioning
confidence: 99%
“…e visualization analysis is conducted on the 3D image recognition residual network. e diversity and accuracy are defined, and comprehensive evaluation is conducted to complete the visualization selectivity analysis of the 3D image recognition residual network [15][16][17]. rough the analysis of residual network visualization in 3D image recognition by composing 3D image recognition residual network visualization based on the particle swarm in the search space, the characteristic vector of the data information on the corresponding 3D image recognition residual network visualization can be expressed in the following form:…”
Section: Svm-knn Network For 3d Imagementioning
confidence: 99%